Relationship between Moral Distress and Quality of Work Life among Nurses in Kerman, Southeast of Iran - Masoumeh Fuladvandi; Gholamreza Fouladvand; Leila Malekyan; Sohila Maleki; Nadia Nourmohammade (نشریه پرستاری ایران, 2025)
Background & Aims Nurses often face ethical challenges in their work place, which can significantly impact their quality of work life (QWL). This study aims to examine the relationship between moral distress and QWL in Iranian nurses. Materials & Methods This descriptive-correlational study was conducted from April to July 2023 in teaching hospitals of Kerman province (Kerman, Bam, Jiroft cities), southeast of Iran. A total of 290 nurses with at least a bachelor’s degree and six months of full-time work experience were selected using a stratified random sampling method. The data collection tools included a demographic form, Corley et al.’s revised moral distress scale (MDS) and the quality of nursing work life scale. Data were analyzed using SPSS software, Version 20, with a significance level set at 0.05. Results The mean score of moral distress was 140.61±43.795, and the mean score of QWL was 155.9±25.077. A moderate negative relationship was observed between moral distress and QWL (R=-0.562, P<0.05), and a weak negative relationship was found between the intensity (R=-0.042, P<0.05) and frequency of moral distress (R=-0.063, P<0.05) and QWL Conclusion The increase in moral distress is associated with a decrease in the QWL among Iranian nurses. Hospital managers should develop policies and interventions for improving the work environment and thus reducing moral distress of nurses.